Implications of groundwater level changes before near field earthquakes and its influencing factors - several earthquakes in the vicinity of the Longmenshan-Anninghe fault as an example - Zhang, Wenxu; Li, Mingqian; Yang, Yao; Rui, Xuelian; Lu, Minggui; Lan, Shuangshuang (Frontiers in Earth Science, 2025)
Characteristics of groundwater level changes may be correlated with subsequent earthquake events. However, the relationship and its determining factors remain unclear. This study examines eight wells situated near the Longmenshan-Anninghe fault zone, which exhibit significant disparities in changes of groundwater level. We quantified these changes by Molchan diagram and investigated factors that may affect it using correlation assessments. The results indicate groundwater levels changes that are more responsive to static stresses and tidal forces also have a high correlation with subsequent earthquake events. Specific leakage, a hydraulic parameter, also effects the correlation between groundwater levels and subsequent earthquakes. Spatial distribution of epicenters may also contribute to differences in this correlation, while aquifer confinement appears to have minimal effect. We used a random forest regression to calculate the comprehensive contribution of these factors to the correlation between groundwater levels and subsequent earthquakes. Notably, epicenter locations showcase the utmost sensitivity to this correlation. These findings can help us understand the complex mechanisms of water level changes before earthquakes and provide insights into the optimal locations for monitoring boreholes.